2016
DOI: 10.1149/2.1091702jes
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Gas Generation, Gas Consumption and Impedance Growth in Li-Ion Cells with Carbonate or Fluorinated Electrolytes Using the Pouch Bag Method

Abstract: Li [Ni 0.42 Mn 0.42 Co 0.16 ]O 2 (NMC442)/graphite pouch cells with an ethylene carbonate-containing or a fluorinated electrolyte were used to prepare charged electrodes for studies using "pouch bags". Sealed pouch bags containing either lithiated graphite or delithiated NMC442 electrodes taken from pouch cells, and also "sister" pouch cells, were subjected to 500 h storage at elevated temperature. The electrodes recovered from the pouch bags and pouch cells after storage were studied using electrochemical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 55 publications
6
90
0
Order By: Relevance
“…Hence, under the present conditions, the CO 2 /oxalate shuttle effect is either negligible or nonexistent and does not contribute to the side reactions in the cell. This is in agreement with Xiong et al, 40,43 who showed that there is no re-generation of CO 2 from a lithium oxalate/CO 2 shuttle detectable in NMC422/graphite cells.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, under the present conditions, the CO 2 /oxalate shuttle effect is either negligible or nonexistent and does not contribute to the side reactions in the cell. This is in agreement with Xiong et al, 40,43 who showed that there is no re-generation of CO 2 from a lithium oxalate/CO 2 shuttle detectable in NMC422/graphite cells.…”
Section: Resultssupporting
confidence: 93%
“…As many commercial-scale cells are vented during or after formation, the high pressure/volume increase is only a matter of the very first cycles. We have further not considered the consumption of CO 2 on the graphite or silicon/graphite anode: Strehle et al 16 showed that up to 40 μmol (≈1 mL) CO 2 can be consumed per square meter graphite surface area during the first formation cycle, which agrees well with previous reports by Xiong et al 40 The graphite electrodes used in the present study have a specific surface area of 0.034 m BET 2 /cm geom 2 , hence 40 μmol/m BET 2 would correspond to a CO 2 consumption of 1.4 μmol/cm geom 2 , which is about ∼20% of the evolved CO 2 (6 μmol/cm geom 2 ). As long as the ratio of lithium oxalate to graphite or the specific surface area of the graphite do not change drastically, the same fraction of CO 2 would also be consumed during formation in other cell formats.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, hydrogen was found in pouch cells, but not pouch bags, suggesting that both electrodes in the cell are required for its appearance. 20 Considering the detrimental effect of gas formation on battery life, Michalak et al 25 suggests that proper cell formation procedure is necessary to improve battery durability.…”
Section: A3470mentioning
confidence: 99%
“…In a series of publications, Dahn and co-workers used gas chromatography (GC-MS and GC-TCD) and a lab-made apparatus based on Archimedes' principle to investigate gas generation during the formation cycles of batteries filled with various electrolyte formulations. [14][15][16][17][18][19][20] The gaseous species were shown to be mostly generated at the onset of the first charging step (i.e., low voltages) and then almost entirely consumed throughout the remainder of the formation period.…”
mentioning
confidence: 99%